'Using humanity to change systems' – understanding the work of online feedback moderation: A case study of Care Opinion Scotland. (March 2022) - Berry, Emma; Skea, Zoë C; Campbell, Marion K; Locock, Louise
Objective: To gain a deeper understanding of online patient feedback moderation through the organisation of Care Opinion in Scotland. Methods: An ethnographic study, initially using in-person participant observations, switching to remote methods due to the pandemic. This involved the use of remote observations and interviews. Interviews were carried out with the whole Scottish team ( n  = 7). Results: Our results identify three major themes of work found in online patient feedback moderation. The first is process work, where moderators make decisions on how to edit and publish stories. The second is emotional labour from working with healthcare experiences and with NHS staff. The third is the brokering/mediation role of Care Opinion, where they must manage the relationships between authors, subscribing healthcare providers and Scottish Government. Our results also capture that these different themes are not independent and can at times influence the others. Conclusion: Our results build on previous literature on Care Opinion and provide novel insights into the emotional and brokering/mediation work they undertake. Care Opinion holds a unique position, where they must balance the interests of the key stakeholders. Care Opinion holds the power to amplify authors' voices but the power to make changes to services lies with NHS staff and services. Online moderation work is complex, and moderators require support to carry out their work especially given the emotional impact. Further research is planned to understand how patient stories are used by NHS Scotland, and the emotional labour involved with stories, from both the author and NHS staff perspective.